Analisis Pelarangan Operasional Tiktok Shop Dalam Langkah Pengambilan Keputusan Melalui Perspektif Problem Tree Analysis - Diana Aviq Rahmadhani; Nadiasel Ogsala; M. Noer Falaq Al Amin (Universitas Sains dan Teknologi Komputer, 2024)
The controversial TikTok Shop case has become a hot topic of discussion lately. The violation committed by the TikTok company is combining online buying and selling platforms with social media platforms. Legally in Indonesia, this is considered illegal and has a negative impact on the sustainability of domestic MSMEs and causes various other problems. The government revised the old Permendag, namely No. 50 of 2020, which did not clearly emphasize the legal PMSE system in Indonesia, which also discussed the social commerce system. The issue of TikTok violating PMSE is an interesting thing to study regarding the relationship between the government's decision to issue a policy to stop TikTok Shop and its driving factors. Researchers use descriptive research methods with a qualitative approach. Literature study and documentation are data collection techniques used in this study. The data analysis technique used is the Problem Tree Analysis approach. While the focus of his research is on PMSE violations by TikTok Companies in Indonesia. From this research, it was found that there is an unclear legal and regulatory umbrella from government regulations regarding PMSE itself. And there are also various consequences caused by TikTok Shop violations that have fatal consequences on the country's economy and domestic MSMEs. For this reason, legal clarity must be paid more attention to by the government so that when there is increasingly rapid technological development as well as increasingly complex systems do not create problems due to technology gaps.